Pengaruh Variasi Porting pada Head Cylinder Terhadap Unjuk Kerja Mesin Sepeda Motor 4 Langkah 110 CC - Warso, Warso; Rekto Prabowo, Nugrah; Nurwibowo, Trio (Accurate: Journal of Mechanical Engineering and Science, 2021)
Improving engine performance can be done by making changes to the cylinder head to increase the volumetric efficiency. The purpose of this study was to determine the effect of ported variations on the cylinder head against the engine performance which includes: airflow, torque, and power, generated by the ported variations on the inlet channel inside the standard cylinder head with the inlet port size of 21.50 mm. The ported variation 1 with a 23.50 mm inlet port diameter, and the ported variation 2 with an inlet port diameter of 25.50 mm. The research method used was an experimental method, carried out on a 4-stroke 110 cc motorcycle. The results obtained indicated the differences in the performance produced, such as airflow, torque, and power in the three variations of the inlet port. In the Cylinder head ported variation 1, the maximum air flow obtained was 30 cfm at 7 mm valve opening. The airflow increased by 3.59% against the standard cylinder head which obtained a maximum airflow of 28.8 cfm at the same valve opening. On the other hand, the cylinder head ported variation 2 obtained a maximum airflow of 27.6 cfm at the same valve opening. It means that the airflow decreased by 4.77% against the standard cylinder head. On ported variation 1 cylinder head, a maximum torque of 8.91 Nm was obtained at 4250 rpm, resulting in the torque increase of 2.49% against the standard cylinder head which obtains a maximum torque of 8.58 Nm at 4500 rpm. With the ported variation 2 cylinder head, maximum torque of 8.15 Nm was obtained at 5750 rpm rotation, which means that the torque decreased by -3.53% against the use of a standard cylinder head. With ported variation 1 cylinder head, maximum power of 7.49 HP was obtained at 7250 rpm and the power increased by 2.41% against the standard cylinder head, which obtained maximum power of 7.27 HP at 7500 rpm. While the ported variation 2 cylinder head, the maximum power obtained was 7.16 HP at 7500 rpm, meaning the decrease in power obtained by -2.76% against the standard cylinder head.